The Capitalization of the Authentic Documents in the Educational Activity of the Primary Cycle - Dorina Chiş-Toia; Dan-Mihai Rohozneanu (Babes-Bolyai University, 2023)
Written, audio or audiovisual documents that were not designed to be used for pedagogical purposes, authentic documents are used by teachers in the teaching activity of different subjects, at different moments/stages of the lesson, aiming at the achievement of the proposed operational objectives, the interaction between pupils, the formulation and expression by them of their own points of view, the teaching staff being the mediator of the discussions. The use of this type of documents gives pupils an authentic picture of the subject in question, contributing to the development of a favorable attitude towards it, positively motivating them to search for similar information, helping them to overcome the limits of the textbook, making them become autonomous in learning. At the same time, the presence of authentic documents makes the lessons more dynamic, encouraging horizontal communication, presupposing on the part of the teaching staff the identification and use of the most effective activities in order to make full use of them. In this article we aim to present to what extent authentic documents are integrated into the didactic activity, which are these, how they are exploited in the primary cycle both by primary cycle teachers/teachers and by physical education teachers and sport, information obtained from the answers formulated by them to the questions in the applied questionnaire.